[Recensão a] Rhiannon Ash (ed.), Tacitus: Annals Book XV. Cambridge Greek and Latin Classics, Cambridge, Cambridge University Press, 2018. 368 pp. - Pimentel, Maria Cristina (2022)
Recensão crítica a comentário ao Livro XV dos Annales de Tácito (CUP).